Low-Temperature Phosphine Fumigation Is Effective Against Drosophila suzukii in Sweet Cherry - Hang Zou; Li Li; Jun Zhang; Baishu Li; Yu Xiao; Yonglin Ren; Ju Huang; Wei Chen; Tao Liu (Insects, 2025)
Drosophila suzukii, classified as a quarantine pest in some countries, poses a serious threat to global trade due to its ability to damage berries and cherries. Recent studies indicate that low-temperature phosphine (PH3) fumigation effectively controls this pest without compromising fresh produce quality. However, the specific protocol for managing D. suzukii larvae in cherries using this method remains underexplored. This study evaluates the efficacy of low-temperature PH3 fumigation in controlling D. suzukii larvae across three cherry varieties at 3 °C and investigates potential effects on key quality metrics. Tolerance assessments revealed that 3rd instar larvae exhibit the highest resistance to PH3 among all developmental stages. A concentration of 800 mL/m3 PH3 for 84 h at 3 °C achieved phytosanitary efficacy for 0.99997 with no negative effect on the quality attributes of the tested cherry varieties. These results support low-temperature PH3 fumigation as a viable postharvest treatment for D. suzukii management in sweet cherries.